Comparison of Irrigation with Povidone-Iodine Versus Normal Saline on Wound Infection After Open Appendectomy - Muhammad Abid Owais; Syed Ali Haider; Sidra Abbas; Khalid Ahmed; Saeed Ahmed; Akram Rajput (KARACHI MEDICAL AND DENTAL COLLEGE, 2019)
Objective: Surgical site infections (SSIs) pose a continued problem to operating surgeons. It adds to        the healthcare cost, increases morbidity and  mortality  and  sometimes  culminates  in  re-explorations.  Rate of SSIs can be ameliorated by removing damaged or  non-viable  tissue,  metabolic  waste  and  wound exudates; this can be achieved by irrigation of surgical wound intraoperatively. Surgical wound irrigation can also be performed postoperatively. Even after giving prophylactic antibiotics and august aseptic measures, post-appendectomy wound infection remains soaring.  The  efficacy  of  povidone-io- dine on non-incised skin is well known  but  its  application  as  an  intraoperative  irrigation  solution  in  open surgical wounds is not a mundane practice. Likewise prophylactic irrigation with  normal  saline solution to prevent wound infection has also turned out to be effective in some studies. The objective           of this study is to compare the percentage of superficial SSI post-appendectomy, with intraoperative irrigation of subcutaneous plane using 1% povidone-iodine solution versus normal saline. Methods:  200 cases of open appendectomy for acute appendicitis at Baqai Medical University, Kara-       chi were randomly distributed into two arms. In group A, 0.9% Normal Saline was employed to irrigate subcutaneous tissue before skin closure while in group B irrigation with 1%  diluted  povidone-iodine  solution was undertaken. The cases were assessed for infection in surgical wounds in line with Southampton wound grading system for five days after surgery and followed for thirty days. Results: Mean age of participants of this study was 18.65 years.  There  were  100  patients  in  both  groups and the groups were not different statistically in terms of age, gender and operative findings. A     total of 38 (19%) out of 200 patients had Southampton grade 2 and above, signifying wound infection.      Out of these, 29 (29%) were from Group A and 9 (9%) from Group B (p=0.001). Conclusion: 1% diluted povidone-iodine irrigation of subcutaneous plane after appendectomy remark-   ably lowers the rate of SSI when compared with normal saline irrigation.